2010
DOI: 10.1016/j.jaci.2010.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lymphocyte subsets in HIV-infected, long-term nonprogressor, and healthy Asian children through 12 years of age

Abstract: Background There are limited data on the immune profiles of HIV-positive children, compared with healthy controls, and no such data for Asian children. Objectives To immunophenotype HIV-positive Asian children, including long-term non-progressors (LTNPs), compared with age-matched healthy controls. Methods We used flow cytometry to analyze 13 lymphocyte and monocyte subsets from 222 untreated, HIV-positive children with 15%–24% CD4+ T cells and no AIDS-related illnesses and 142 healthy children (controls).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
5

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 32 publications
(55 reference statements)
1
30
0
5
Order By: Relevance
“…We and others have reported that lymphocyte patterns are affected by ethnicity, gender and environmental factors 1-3 . Differing exposure to infectious agents such as malaria, tuberculosis and cytomegalovirus could underlie differences in lymphocyte subsets patterns in contrasting settings 4-6 .…”
Section: To the Editormentioning
confidence: 83%
See 2 more Smart Citations
“…We and others have reported that lymphocyte patterns are affected by ethnicity, gender and environmental factors 1-3 . Differing exposure to infectious agents such as malaria, tuberculosis and cytomegalovirus could underlie differences in lymphocyte subsets patterns in contrasting settings 4-6 .…”
Section: To the Editormentioning
confidence: 83%
“…Differing exposure to infectious agents such as malaria, tuberculosis and cytomegalovirus could underlie differences in lymphocyte subsets patterns in contrasting settings 4-6 . In this study, we analyzed combined data from three studies of healthy children from Thailand 1 , Malawi 2 and the USA 3 that had used similar standard flow cytometric methods and markers, thus allowing assessment of immune heterogeneity across settings with differences in ethnicity and infectious disease exposure.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry was performed at baseline by methods previously described for the following cell subsets: activated CD4 (CD4 + 38 + DR + ) and activated CD8 (CD8 + 38 + DR + ) T cells [6]. C Reactive Protein (CRP) was measured using the CRP High Sensitive Assay (Cobas Integra System, Roche Diagnostic Systems, Basel, Switzerland).…”
mentioning
confidence: 99%
“…inhaled budesonide, unspecified oral/inhaled bronchodilator, and salbutamol + budesonide) (12.5%). Median (IQR) durations of medications use were 16 (10-41) days for salbutamol, 7 [5][6][7][8] days for terbutaline, 167 (34-427) days for budesonide, and 5 [2][3][4][5][6] days for bronchodilator with no differences between arms (all p N 0.2).…”
mentioning
confidence: 99%